Tamaño De Puesta, Sitios De Nidificación Y éxito Reproductivo Del Caiquén (Chloephaga Picta Gmelin, 1789) en La Reserva De Biosfera Cabo De Hornos, Chile - Ibarra, J. Tomás; Schüttler, Elke; McGehee, Steven M.; Rozzi, Ricardo (Anales del Instituto de la Patagonia, 2009)
This article studies the breeding biology of the Upland Goose (Chloephaga picta) in terms of clutch size, nesting sites, and breeding success as a function of habitat variables on Navarino Island, Cape Horn Biosphere Reserve, Chile.